2011
DOI: 10.1007/s11434-011-4469-0
|View full text |Cite
|
Sign up to set email alerts
|

Northern Tibetan Plateau cooling and aridification linked to Cenozoic global cooling: Evidence from n-alkane distributions of Paleogene sedimentary sequences in the Xining Basin

Abstract: The Xining Basin on the northeastern Tibetan Plateau holds the longest continuous Cenozoic stratigraphic record in China. The sequence record contains considerable information on the history of Tibetan uplift and associated climatic change. In particular, high resolution n-alkane biomarker proxy and pollen records have been obtained from the Paleogene sediments of the Xiejia section of the basin. A combination of the n-alkane and palynological records reveals that the paleoclimate in the Xining Basin experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 52 publications
2
18
0
1
Order By: Relevance
“…The variation around 130 kyr further confirms the double impact of microbial degradation and vegetation changes on organic matter Long et al, 2011). The n-Alkane parameters C31/C27 and C31/(C27+C29+ C31), in the Lingtai loess section indicate an increase of herbs in the middle of the Chinese Loess Plateau at 130 kyr BP.…”
Section: Proxy Indicators Of Vegetation Change In the Lingtai Sectionmentioning
confidence: 53%
See 2 more Smart Citations
“…The variation around 130 kyr further confirms the double impact of microbial degradation and vegetation changes on organic matter Long et al, 2011). The n-Alkane parameters C31/C27 and C31/(C27+C29+ C31), in the Lingtai loess section indicate an increase of herbs in the middle of the Chinese Loess Plateau at 130 kyr BP.…”
Section: Proxy Indicators Of Vegetation Change In the Lingtai Sectionmentioning
confidence: 53%
“…Over the past few decades, researchers have studied past vegetation and climate changes throughout different periods from sediments on the Chinese Loess Plateau with various methods, such as soil microstructure (Guo et al, 1993), sporopollen in loess deposits (Liu and Su, 1994;Sun et al, 1997;Wu et al, 2004;Long et al, 2011), phytoliths (Lv and Liu, 1999), and stable carbon isotopes (Ding and Yang, 2000;Gu et al, 2003;Zhang et al, 2003;Vidic and Montanez, 2004;Liu et al, 2005;Rao et al, 2006;Chen et al, 2006;Zhou et al, 2009Zhou et al, , 2014Yang et al, 2012). This previous research has generally found that grassland vegetation on the CLP was a mixture of C 3 and C 4 herbaceous plants, with a dominance of C 3 plants since late Quaternary, and at no previous time was the CLP dominantly forested (Gu et al, 2003;Zhang et al, 2003;Zhou et al, 2009;Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…C 29 is the dominant peak on the GC chromatography. C 29 homologs is dominant in needle leaved evergreen trees, while C 27 homologs is dominant in broad-leaf trees (Long et al, 2011). Sample ABY-13 from Ağaçbaşı peat comprises both n-alkale homologs but C 29 homologs are dominant.…”
Section: N-alkanes Tar Cpi Pwax Paq and Acl Valuementioning
confidence: 97%
“…However, there is an increasing availability of terrestrial sedimentary archives of the Eocene. These sites are located on the northeastern margin of the Tibetan Plateau (Bosboom et al, ; Chi et al, ; Dai et al, ; Horton et al, ; Long et al, ; Miao et al, ; Sun et al, ; Yue et al, ), in central China (Bowen et al, ; Ting et al, ; Zhu et al, ), northeastern China (Chen et al, ), southwestern China (Li et al, ; Su et al, ), North and South America (Hyland et al, ; Hyland et al, ; Hyland & Sheldon, ; Koch et al, ; Krause et al, ), and Europe (Egger et al, ). Research on these Eocene sections has focused mainly on chronology and specific climatic events, whereas few studies have drawn stratigraphic comparisons between different sections (Fang et al, ; Smith et al, ).…”
Section: Introductionmentioning
confidence: 99%